Pageoph Topical Volumes
DOI: 10.1007/3-7643-7585-x_9
|View full text |Cite
|
Sign up to set email alerts
|

Phase and Correlation in ‘Random’ Seismic Fields and the Reconstruction of the Green Function

Abstract: Abstract-We first present a summary of recent results on coda interpretation. We emphasize the observation of the stabilization of P to S energy ratio indicating the modal equipartition of the wavefield. This property clearly shows that the coda waves are in the regime of multiple scattering. Numerical solutions of the elastic radiative transfer equation are used to illustrate the evolution of the wave-field towards P-to-S energy stabilization, and asymptotically to complete isotropy. The energy properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 97 publications
0
33
0
Order By: Relevance
“…A second possibility is that the attenuation coefficients we obtained include scattering attenuation in addition to intrinsic attenuation [ Brandenburg and Snieder , 1989; Romanowicz , 2002; Spetzler et al , 2002], while direct P and S waves are affected less by scattering. The effects of scattering in the coherency are indistinguishable from that of intrinsic attenuation as we processed the data [ Weaver and Lobkis , 2006; Campillo , 2006]. Nevertheless, because scattering should be strongest at shallow depths within the basin, and those results agree between the studies, scattering is not likely the cause of the discrepancy.…”
Section: One‐dimensional Phase and Q Model Inversionmentioning
confidence: 94%
“…A second possibility is that the attenuation coefficients we obtained include scattering attenuation in addition to intrinsic attenuation [ Brandenburg and Snieder , 1989; Romanowicz , 2002; Spetzler et al , 2002], while direct P and S waves are affected less by scattering. The effects of scattering in the coherency are indistinguishable from that of intrinsic attenuation as we processed the data [ Weaver and Lobkis , 2006; Campillo , 2006]. Nevertheless, because scattering should be strongest at shallow depths within the basin, and those results agree between the studies, scattering is not likely the cause of the discrepancy.…”
Section: One‐dimensional Phase and Q Model Inversionmentioning
confidence: 94%
“…The ratio depends on the scattering and absorption properties. A stabilized energy ratio is a good indicator “that the field is entering a regime in which total energy is described by a diffusion and will therefore evolve towards equipartition and isotropy” [ Campillo , 2006]. However, the diffusion approximation largely underestimates flux anisotropy [ Paul et al , 2005].…”
Section: The Ambient Seismic Wave Fieldmentioning
confidence: 99%
“…The diffuse wave field associated with scattering approaches—at long lapse times with respect to the pulse‐source event—equipartition [ Campillo and Paul , 2003; Paul et al , 2005]. In this asymptotic regime all possible modes are randomly excited with equal weight on average [e.g., Campillo , 2006, and references therein], and energy ratio markers are equilibrated. In contrast to pulse‐sources, continuously acting sources can also lead to a stabilization of energy markers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently demonstrated that the time cross‐correlation function of random seismic wavefields such as seismic coda [ Campillo and Paul , 2003] or seismic noise [ Shapiro and Campillo , 2004] computed between a pair of distant stations contains, at least partially, the actual Green function between the two stations [ Campillo , 2006]. This provides us with a possibility to retrieve the propagation properties of deterministic seismic waves along long paths by analyzing microseisms only.…”
Section: Introductionmentioning
confidence: 99%